Pembubaran Partai Politik Dari Kaca Mata Hak Asasi Manusia Dalam Bingkai Rule Of Law - Anti Navirotul Baety; Heni Dora Sinaga; Ibrahim Yahya (Lembaga Pengembangan Kinerja Dosen, 2023)
Indonesia is a country that upholds people's sovereignty, which means that all political and governmental activities in Indonesia, both directly and indirectly, are regulated by the people. It is the people who choose who is entitled to occupy government positions using the election mechanism. This election itself was followed by more than a dozen political parties. The purpose of conducting this research is to further discuss whether the dissolution of political parties has violated the existence of freedoms that guarantee human rights in them or whether these rights have limitations in certain respects. As well as another objective is to examine the reasons and mechanisms in a dissolution within a political party carried out by the Supreme Court. This research uses normative qualitative methods where the results of the research will be in the form of a comprehensive review based on law no. 24 of 2003 and Law no. 2 of 2008. The result is that the dissolution of political parties does not violate human rights at all because the right to associate has certain limitations and the reason political parties can be dissolved is that it is contrary to the 1945 Constitution and Pancasila ideology.